Representação social de saúde bucal de usuários do sistema público de saúde de Vitorino - PR - Yamada, Raquel Tieko Tanaka (2012)
Oral health can have a different definition for each context and each social group. For some dental professionals, it may represent cavity-free, perfectly aligned teeth in good occlusion; for others, it may represent a person integrated into society, satisfied with his or her mouth’s functions. Oral health, for each individual, can also change over the years, from its life cycles, its problems and the environment in which it’s in. Understanding what oral health represents is to understand a little about people’s needs and daily lives. Getting inside the daily life of a group of people and extract the meaning of oral health from it requires the use of reliable and safe resources under the perspectives of ethics and science. The theory of Social Representations, proposed by Moscovici in 1961, which seeks to understand the concepts in the common sense, through the ideas, values and practices of everyday life of a social group, was the basis of this study. The DIDL (Dental Impact on Daily Living) tool, developed by Leão in 1995, the DMFT (Decayed, Missing and Filled Teeth) index, a semi-structured survey and interview, served as a guide for the identification of Social Representations of Oral Health in Adult Users of the Public Health Services of Vitorino. The concern over understanding how this social group loses so many dental elements was what sparked interest in this research. The research population was obtained by temporal sample of adults in the 35 to 44 age group, who sought public health services to receive dental treatment. In total, 40 individuals participated in all stages of research, 20 being female and 20 male, the median household income was 2.40 times the minimum wage, with an average of 6.88 years of education, and an occupation that allowed for flexibility in working hours, such as homemakers, farm workers and drivers. The results point to a picture of health inequity. According to the World Health Organization’s Classification, the DMFT index value of 20.50 found for the group is considered high for values above 13.9 for this age group. The reliability coefficient for the 36 questions in the DIDL, obtained through the Crombach’s alpha, was 0.909. The DIDL results showed that 22.5% of users were dissatisfied, 60% relatively satisfied and 17.5% satisfied with their oral health. It was observed that access to public health services during childhood and adolescence, the remedial-restorative paradigm of dental practices, and the socio-demographic conditions were determining factors leading to a framework of inequity in oral health (or just health), and led them to complain of great pain during their lives. The hypothesis that users lose their teeth due to lack and/or difficulty of access is proven by the account of the users and the level of oral health in which they find themselves. Within the framework of inequity, there were still inequalities regarding the group of dissatisfied, which presented higher DMFT, lower income, lower educational level, and higher age average; they were the ones that reported more pain and were more incisive in their complaints. The social representations of oral health of the social group, as a whole, were conceived by them as “not feeling pain”. Concept of oral health that can be understood as one in which the disease is perceived as an “occupation”, i.e., that one can fight against the disease, that can be treated, is not destructive, is feared for the pain, but is always accepted by this social group.